1997
DOI: 10.3136/fsti9596t9798.3.357
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Lipid Modified Lipase for Interesterification and Hydrolysis Reactions in n-Hexane.

Abstract: Lipase modification by addition of lipid is a simple and effective way to greatly improve enzyme activity for n-hexane based interesterification and hydrolysis reactions. The ranges of modifying lipids and lipases were evaluated, with stearic acid and lipase Saiken 100 (Rhizopus japonicus) investigated in more detail. Enzyme protein recovery and activity were influenced by the quantity of stearic acid addition and the pH of the aqueous preparation phase. Modified lipase protein was characterized using SDS-PAGE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

1998
1998
2005
2005

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 24 publications
1
9
0
Order By: Relevance
“…The solution containing SA had the highest adsorption profile, followed by lipase buffer, which in turn was higher than the lipase water solution (circles). These data support previous studies (8,29) where protein recovery was favored with acidic Tris buffer (5 mmol/L) and by the presence of SA. SA therefore promotes the recovery of protein during ML preparation, which implies that fatty acid and ionic interactions are important for the binding of enzyme and carrier over the range of loading concentrations tested.…”
Section: Resultssupporting
confidence: 93%
“…The solution containing SA had the highest adsorption profile, followed by lipase buffer, which in turn was higher than the lipase water solution (circles). These data support previous studies (8,29) where protein recovery was favored with acidic Tris buffer (5 mmol/L) and by the presence of SA. SA therefore promotes the recovery of protein during ML preparation, which implies that fatty acid and ionic interactions are important for the binding of enzyme and carrier over the range of loading concentrations tested.…”
Section: Resultssupporting
confidence: 93%
“…Vegetable oils and animal fats usually contain water [15]. To examine the effect of water on the transesterification of triolein with methanol, water was added directly to the reaction solution.…”
Section: Effect Of Water On Catalytic Activitymentioning
confidence: 99%
“…The effects of reaction variables such as the molar ratio of methanol to triolein on the yields of the reaction products; methyl oleate and glycerol, are examined. Further, the effect of water on the catalytic activity of the catalyst is also investigated, as vegetable oils and animal fats usually contain water [15] and this material may affect the catalytic activity of this system.…”
Section: Introductionmentioning
confidence: 99%
“…In other words, some of the modified lipases with low interesterification activity contained a significant amount of the active (for hydrolysis) lipase molecule. This suggests that lipase activation for interesterification is associated with the environment or molecular conformation of the lipase [9] and not to purification of the "active" protein [8]. It has been reported that lipases are activated at the oil-water or a hydrophobic interface so as to catalyze lipid hydrolysis [16][17][18][19], which involves a conformational change of the lipase structure [20,21].…”
Section: Effect Of Fatty Acid On Lipase Activationmentioning
confidence: 99%
“…Previously, we reported a fatty acid modification method that improved the transesterification activity of some lipases in organic solvents [8,9]. These lipase-fatty acid complexes exhibited high interesterification activity in nhexane.…”
Section: Introductionmentioning
confidence: 99%